Bioaerossóis bacterianos em um hospital - Pereira, R. G.; Reis, D.; Ambrósio, G. N.; Raddi, Maria Stella Gonçalves [UNESP]; Pedigone, M. A M; Martins, C. H G (My University, 2005)
Microbial contamination of an enclosed area may come from outside or be generated within the area itself. In the study described here, bioaerosol levels in hospital air were quantified and related to those found in the air outside, taking into account some of the environmental variables that affect air quality, such as the number of occupants of a room and the type of ventilation. Airborne bacteria were collected for five minute by blowing air at 500 L min -1 in high speed jets on to the surface on plates culture in a single-stage bioaerosol impactor. The mean viable count of bacteria in the air outside in the hospital, São Paulo State, was 77 ± 4 CFU m -3, while in the air inside the hospital it was 302 ± 260 CFU m-3. The operating theatre was the only space sampled with a controlled environment and, after orthopedic surgery, it had the highest bioaerosol count recorded (867 ± 482 CFU m-3). In the enclosed environments, nine bacterial species were identified. Despite the difficulty in establishing precise numbers of bacteria in the bioaerosols in hospital environments, the values obtained demonstrate a need to instigate suitable programs to keep the microbial density low in these environments, and eliminate microorganisms presenting a significant risk to their occupants. It is also recommended that such programs include the monitoring of hospital air, with the aim of defining standards for acceptable numbers of bacteria in the bioaerosol.

A contaminação microbiológica de ambientes internos é afetada pela presença de bioaerossóis do ambiente externo e as geradas no próprio ambiente. O objetivo deste trabalho é relacionar a concentração de bioaerossóis encontrados em ambientes internos de um hospital em relação ao ar exterior, levando em consideração alguns parâmetros ambientais que influenciam na qualidade do ar, como número de ocupantes e tipo de ventilação. Quinhentos litros de ar foram coletados, por impacto, durante cinco minutos, utilizando-se um amostrador de ar de um estágio sobre placas de meios de cultura. A concentração média de bioaerossóis bacterianos viáveis no ambiente externo de um hospital do interior do Estado de São Paulo foi de 77 ± 4 UFC/m3 e no ambiente interior de 302 ± 260 UFC/m3 de ar. O centro cirúrgico, após cirurgia ortopédica, único ambiente climatizado amostrado, apresentou a maior concentração (867 ± 482 UFC/m3). Nos ambientes interiores nove espécies bacterianas foram identificadas. Apesar da dificuldade em se estabelecer valores para a concentração de bioaerossóis bacterianos em ambientes hospitalares, os resultados demonstram a necessidade de programas apropriados para a manutenção da concentração microbiana baixa nesses ambientes e ausência de microrganismos que possam significar risco para os seus ocupantes. O monitoramento do ar deveria ser recomendado objetivando definir quantidades aceitáveis de contaminantes bacterianos. Palavras-chave: Bioaerossol, infecção Hospitalar, ar hospitalar.
Bacterial bioaerosols in hospital
Keywords: Bioaerosol; Hospital air; Nosocomial infection; aerosol; air pollution; bacterium culture; environment; hospital; human; microbial contamination; operating room; risk factor